Cost and benefit of apprenticeship training: a comparison of Germany and Switzerland - Regina Dionisius; Samuel Muehlemann; Harald Pfeifer; Günter Walden; Felix Wenzelmann (Institute for the Study of Labor (IZA), 2008)
For the first time it has been made possible to merge a German and a Swiss firm-level data set that include detailed information about costs and benefits of apprenticeship training. Previous analyses based only on aggregate data showed that the net costs of training apprentices are substantial in Germany, whereas apprenticeship training is on average profitable during the training period for firms in Switzerland, even though the two training systems are rather similar. This paper analyzes the reasons for these differences with matching methods. We simulate the impact of changes in certain parameters such as wages, apprenticeship system-related factors and allocation of tasks to apprentices on the cost-benefit ratio using the counterfactual values of the other country. The results show that most of the difference in the net costs of training between the two countries can be explained by a higher share of productive tasks allocated to apprentices in Switzerland and the differences in relative wages.
urn:nbn:de:101:1-20080421224
Keywords: J24; 330; Apprenticeship training; cost and benefit analysis; Duale Berufsausbildung; Kosten-Nutzen-Analyse; Vergleich; Deutschland; Schweiz